Finite difference method based analysis of bio-heat transfer in human breast cyst. (May 2019) - Patil, Himanshu Madhukar; Maniyeri, Ranjith
Highlights: Numerical study on bio-heat transfer in human breast cyst using finite difference method. One, two and three-dimensional modeling of bio-heat transfer problem. Effect of location of cyst and location of cyst. Simulation of multiple cysts. Results helpful for early detection of cancer. Abstract: Bio-heat transfer is a branch of bio-medical engineering which has its foundation linked to engineering disciplines of heat transfer. The thermal properties and behaviour of various malfunctioning tissues in human body varies as compared with normal tissues. Among various cancer tissues one which is commonly diagnosed in women is breast cyst (cancer causing fluid). The aim of present work is to develop one, two and three-dimensional computational models to study bio-heat transfer problems using finite difference method. First of all, a numerical model based on finite difference method is developed to solve Pennes's bio-heat transfer equation in one-dimension to get temperature profiles normal to skin surface and validated with existing analytical solutions. Secondly, the numerical model is extended to study the thermal behaviour of human breast section embedded with cyst using two-dimensional cylindrical coordinate systems and validated with previous researcher's results. The effect of size, location and presence of multiple cysts on surface temperature is studied. Lastly, the work is extended for the case of three-dimensional breast section with cyst located at the centre. The numerical results obtained using one, two and three-dimensional computational models will be highly helpful in the early detection of breast cancer tissues and also the location of it inside the body.